2016
DOI: 10.20892/j.issn.2095-3941.2016.0058
|View full text |Cite
|
Sign up to set email alerts
|

Primary peritoneal carcinoma metastasizing to breast: a single case report and literature review from clinic to biology

Abstract: Primary peritoneal carcinoma (PPC) is a type of rare malignant epithelial tumor. Metastasis from PPC to breast has been rarely reported. PPC originates de novo from the peritoneal tissues rather than invasion or metastasis from adjacent or remote organs. PPCs have been implicated in many cases of carcinomas of unknown primary origin. It is similar to ovarian cancer (OvCa), because it shares the same common embryonic origin, the coelomic epithelium (mesodermal origin). The mechanism of oncogenesis remains elusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…In a further three cases a metastatic spreading to the breast and/or axillar lymph nodes has been described. In these cases, it was important to distinguish PPSPC from primary breast cancer and its metastases [10]. Our case did not show any retroperitoneal lymph node metastases, neither at the initial CRS and HIPEC procedure nor in the follow-up CT scans.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…In a further three cases a metastatic spreading to the breast and/or axillar lymph nodes has been described. In these cases, it was important to distinguish PPSPC from primary breast cancer and its metastases [10]. Our case did not show any retroperitoneal lymph node metastases, neither at the initial CRS and HIPEC procedure nor in the follow-up CT scans.…”
Section: Discussionmentioning
confidence: 58%
“…In case of lymph node involvement, Dubernard et al [8] showed that lymphadenectomy seemed to be beneficial in a small series of 19 patients and reported an overall survival of 83% after 3 years. In few cases breast and/or axillar lymph node metastases have been reported; however, it is of great importance to differentiate these from primary tumors of the breast [9,10]. …”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] The typical morphologic features of MOCB include a localized mass with microlobulated margins and posterior enhancement on ultrasound and a well-circumscribed growth pattern surrounded by a fibrous pseudo-capsule, with clear absence of an in situ component. 14 Primary peritoneal serous carcinoma (PPSC) is morphologically and phenotypically similar to ovarian carcinoma (OC), 4 and usually spreads superficially in the peritoneal cavity. It also metastasizes to the liver, lung, brain.…”
Section: Case Presentationmentioning
confidence: 99%
“…1 Metastasis of ovarian or peritoneal serous carcinoma to the breast and/or axillary lymph nodes is rare and is as a late phenomenon associated with the development of disease at multiple sites. 4,5,6 Secondary breast malignancies are rare representing <1% of all breast tumors, but their recognition and distinction from mammary carcinoma are important because the treatment and prognosis differ significantly. When clinical history is not known at the time of diagnosis, both clinical and pathological misdiagnoses are possible, especially when the histological growth pattern can mimic a primary breast carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…EOPPC commonly presents with gastrointestinal symptoms, abdominal distension and pain (secondary to malignant ascites), and respiratory complaints are uncommon at presentation [7]. Metastasis in EOPPC occurs mainly transperitoneally but may also occur by lymphatic and haematological routes; and metastases to cervical lymph nodes, the breast, the brain and the lungs have been reported in the literature [10][11][12][13].…”
Section: Mpe Involves Invasion Of Malignant Cells Into the Pleural Ti...mentioning
confidence: 99%